A supply chain performance measurement improved with integrated methods FDSM, MOO and DEA Part I: A conceptual of performance measurement framework in Thailand: Frozen shrimp chains - Pungchompoo S. (2017)
Supply chain performance measurement has become a popular topic. However, the existing performance measure model still lacks providing interaction aspects of key performance indicators (KPIs) and measuring. The aim of this paper is therefore to propose the conceptual of performance measurement. It can be categorized into the five dimensions which are represented in term of Cost, Flexibility, Responsiveness, Quality, and Innovativeness. For next research study, after the data collection process, researchers will calculate and analyze data by using the fuzzy design structure matrix (FDSM) method for grouping KPIs in term of the interaction among KPIs. ©2010 IEEE.